EMBODIED EXPERIENCES SAAT BERJALAN DAN BERLARI DI RUANG PERKOTAAN : STUDI KASUS KAWASAN SCBD JAKARTA - Taufan Sabastian; Achmad Hery Fuad (NALARs, 2026)
Urban environments fundamentally shape how people perceive and experience space through their senses. Understanding this relationship is crucial for designing cities that actively support human well-being. This study examines how spatial structures and multisensory perceptions influence comfort, motivation, and psychological restoration among individuals engaging in walking and running within Jakarta’s Sudirman Central Business District (SCBD). A qualitative participatory approach was employed, combining direct observation, semi-structured interviews, and reflection to capture embodied sensory experiences. SCBD was selected as a representative high-density urban area that has recently transformed into one of Jakarta’s most popular destinations for running and morning walks on weekends. Findings reveal that spatial enclosure created by building facades, shade from trees and structures, and rhythmic alternations between open and enclosed street segments significantly enhance sensory comfort and spatial orientation. Participants also expressed higher motivation to engage in physical activity when visual diversity and greenery were present, indicating that hybrid environments combining urban form and natural elements can foster restorative and socially vibrant experiences. These results underscore the importance of context-specific, multisensory design strategies in shaping urban spaces that promote active, psychologically engaging, and socially connected lifestyles.